Intellectualising African languages in literature and linguistics at selected Zimbabwean higher learning institutions - Nhongo, Raphael; Siziba, Liqhwa (South African Journal of African Languages, 2024)
The incorporation of specialised domains of knowledge such as STEM subjects into the discourse surrounding the intellectualisation of African languages has become increasingly prevalent. However, scant attention has been given to examining the extent to which the intellectualisation of African languages for the instruction and study of literature and linguistics at institutions of higher learning has progressed. The article argues that prior to focusing on a variety of fields of knowledge, the intellectualisation of African languages should begin with the areas of literature and linguistics. In addressing this argument, a questionnaire containing literature and linguistics terms was distributed to 15 lecturers selected from four institutions of higher learning, comprising two teachers' colleges and two universities in Zimbabwe. The results of the study revealed that literature and linguistics terms for identical concepts in the same language vary across Zimbabwean institutions of higher education. In some cases, even within the same institution, the terms used by lectures for the same concepts differed. It is concluded that the decolonisation of education at higher institutions of learning should begin with the intellectualisation of African languages through the development of standard terminologies for the instruction of literature and linguistics.